A cryptocompression system with Multi-Factor RSA algorithm and Levenstein code algorithm - Budiman, M A; Sihombing, P; Fikri, I A (Journal of physics. Conference series, 2021)
Exchanging digital messages by electronic means has a major security concern. The data being sent can be accessed and read by some unintended parties if there is no security system involved. Cryptography obscures the messages being sent and they can only be read by intended recipients by using the right key. Using asymetric cryptography algorithm such as Multi-Factor RSA may help to obscure a message with high security; however, the ciphertext is usually much larger than the message so it takes much more time to transmit. In order to solve this problem, this research combines the Multi-Factor RSA with the Levenstein Code algorithm in a cryptocompression system to compress the size of the message being sent. This research also compares encrypt-then-compress scheme with compress-then-encrypt scheme. The result shows that encrypt-then-compress scheme has a better compression ratio than the compress-then-encrypt scheme. On the contrary, in terms of actual time performance, the compress-then-encrypt scheme is faster than encrypt-then-compress scheme.